A novel high mechanical and excellent hydrophilic electrospun polyurethane‐silk‐bioactive glass nanofiber film for rotator cuff injury repair. Issue 10 (18th October 2021) - Duan, Kaikai; Ling, Ziao; Sun, Minghui; Zhi, Weiliang; Zhang, Yifeng; Han, Sheng; Xu, Jingli; Wang, Hui; Li, Jiusheng
Abstract: Rotator cuff injury is the most common muscle injury in bone surgery and there was still enormously challenging to completely repair it. Disturbed by mechanical stability and biocompatibility, most implants have failed to relieve symptoms and prevent the development of osteoarthritis. Herein, we have firstly fabricated novel electrospinned nanofiber membranes by integrating the excellent mechanical properties of polyurethane (PU), the good biocompatibility of silk fibroin with the osteogenesis properties of bioactive glass (PSB). The obtained results have exhibited that the PSB nanofiber film possessed excellent mechanical properties with the tensile stress have reached 14.6 MPa and the tensile strain reached 70%, which had extremely remedied the properties of pure silk film (3.8 MPa and the tensile strain 7.9%). Especially, PSB has shown superior hydrophilicity (WCA) than silk (WCA) and PU (WCA) groups. Furthermore, we have endowed the PSB with osteogenesis by doping bioactive glass (BG) in it. The PSB film can long‐term release functional ions (Si and B ions) that benefit bone tissue repair, and the CCK‐8 and ALP results have also confirmed the excellent biocompatibility and osteogenesis of PSB. Hence, the novel PSB film may provide a new treatment strategy for repairing rotator cuff injury. Abstract : Electrospinning was a high‐voltage electrostatic field that allowed the polymer solution to overcome its own surface tension and viscoelastic force, accompanied by solvent volatilization or melt cooling and solidification, and finally fall on the collecting plate to form fibers and accumulate into a film. Electrospun membranes should own both biocompatibility and mechanical properties when used as biomaterials. This article improves the mechanical properties and biocompatibility of the membrane through physical mixing, and at the same time can release functional ions to promote tissue repair. Cell experiments have proved the potential of this material as a biological material.